Two new species of the genus Polyphrix Townes 1972 (Hymenoptera, Ichneumonidae, Cryptinae) from Peru - Inga, Lita; Alvarado, Mabel (Zootaxa, 2024)
Polyphrix is a small neotropical genus comprising four species. Here, two new species from Peru are described and figured: Polyphrix misa sp. nov. and Polyphrix tullu sp. nov. The distribution of P. varians Townes 1970 in Peru is confirmed and P. stellata Tedesco & Santos 2009 is newly recorded for the country. Additionally, an updated key to species is presented.